PENGARUH MEDIA PEMBELAJARAN SOFTWARE PROTEUS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENERAPAN RANGKAIAN ELEKTRONIKA KELAS XI DI SMK NEGERI 1 JETIS - Maniar, Tiara; Rusimamto, Puput Wanarti; Sulistyo, Edy; Fransisca, Yulia (Universitas Negeri Surabaya, 2021)
The research was conducted in SMK Negeri 1 Jetis where the learning process requires media so that students can learn independently to support the activities of the practicum. This study uses a learning media that the software proteus. The purpose of this research is: (1) determine differences in student learning outcomes before the application and after the application of learning media software proteus, (2) determine the response of students to the eye pelejaran the application of the electronic circuit. The method of research is Pre-Experimental Design with the shape of the One-Group Pretest-Posttest Design. The technique of data analysis using the t test to determine differences in learning outcomes and student responses using a sheet of the questionnaire. The validation sheet filled by two faculty of Electrical Engineering and one teachers of SMK. This research resulted in the discussion, namely: (1) Differences in learning outcomes of students by using the t test obtained value of 0.000 and the level of significant was set at 0.05 so that the value of 0,000<0,05 means that H0 is rejected and H1 is accepted. So there is a significant difference between the learning outcomes of students before and after the application of learning media software proteus. (2) the Response of students to obtain the average worth 82% of which consists of 3 aspects, namely aspects of interest, the material and the suitability of the efforts of the subjects. So the average is classified in the category of very good for the students ' response to the subjects. Learning Media can be used as effective media so that students do not feel bored with the material being taught.